2005
DOI: 10.2105/ajph.2004.057612
|View full text |Cite
|
Sign up to set email alerts
|

Moving Forward in Fall Prevention: An Intervention to Improve Balance Among Older Adults in Real-World Settings

Abstract: Structured, group-based exercise programs offered by community organizations in natural settings can successfully increase balancing ability among community-dwelling older adults concerned about falls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
41
1
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 32 publications
5
41
1
3
Order By: Relevance
“…It is well known that falls are a significant predictor of decline in performance of IADLs and ADLs, placement in a nursing home, and illness (Robitaille et al, 2005;Tinetti, Bogardus, & Agostini, 2004). Our study lends yet more support to the urgency of allocating resources for home-based fall-risk assessment and fall prevention as one way of potentially reducing functional decline and nursing home placement, especially because more than one third of those individuals 65 years of age and older fall each year (Robitaille et al).…”
Section: Discussionsupporting
confidence: 60%
“…It is well known that falls are a significant predictor of decline in performance of IADLs and ADLs, placement in a nursing home, and illness (Robitaille et al, 2005;Tinetti, Bogardus, & Agostini, 2004). Our study lends yet more support to the urgency of allocating resources for home-based fall-risk assessment and fall prevention as one way of potentially reducing functional decline and nursing home placement, especially because more than one third of those individuals 65 years of age and older fall each year (Robitaille et al).…”
Section: Discussionsupporting
confidence: 60%
“…The multisensory training conducted in a group might have contributed to the improvement in balance. Akin to this study, Robitaille et al (2005) showed that exercise programmes performed in groups improved the balance of the elderly in the community. Wayne et al (2004) reported that the improvement of vestibular function and the possible linkage of psychological well-being may probably be the adjuvant mechanism of balance improvement.…”
Section: Discussionmentioning
confidence: 71%
“…Robitaille et al [46] developed a multifaceted group based fall prevention programme for older independent adults with a history of falls or who worried about their balance, finding that the intervention significantly improved static balance and mobility. It was concluded that structured, group-based exercise programmes offered by community organisations in natural settings can successfully increase balancing ability among older adults concerned about falls.…”
Section: Types Of Physical Activitymentioning
confidence: 99%